Mussolini's dream factory : film stardom in fascist Italy - Gundle, Stephen, 1956- (Berghahn Books, 2013)
This book offers the first extended analysis of film stardom in Fascist Italy, focusing on the period from the start of sound cinema to the final end of Fascism in 1945. The author examines the development of an Italian star system, evaluates its place in film production and distribution, and explores its relationships with the political sphere and with broader commercial culture. The popular press, along with other evidence, is used to assess the extent of public engagement with film stars. Several major stars, including Isa Miranda, Vittorio De Sica, Amedeo Nazzari and Alida Valli, are cl.